KENDALA ADOPSI BENIH BERSERTIFIKAT UNTUK USAHATANI KENTANG (Forum Penelitian Agro Ekonomi, 2024)
Most potato farmers in Indonesia do not adopt certified potato seed. Relatively expensive price of certified seed is the main reason the farmers apply the seed produced by themselves. In general, prices of potato produced using certified seed and those produced using uncertified seed are relatively equal. The farmers who regularly apply certified seed are those having partnership with the potato processor. High risk of potato seed production discourages the certified seed producers to produce it in sufficient amount for market supply. Less cost of certified seed production and improved potato selling price will enhance farmers’ adoption of certified seed. The government needs to empower the farmers to produce quality seed by themselves through informal seed system development rather than they have to depend on commercial certified-seed produced by the formal seed industry.